The Importance of Technology of Canning Goji Berries in Food Industry - Ismanova Azima Dolimjon qizi; Karimjonov Jabroil Komiljon ogli (Genius Journals, 2022)
This article describes the methods and technology of processing Goji fruit, as well as its economic efficiency, which describes the products used in industry to make compotes, jams and jams from Goji fruit, their quantity and technology. The useful properties and chemical composition of the finished product are also described
Keywords: Goji; processing methods; technology; jam